Synovial Sarcoma of Peripheral Nerves: Analysis of 15 Cases. (August 2017) - Chrisinger, John S.A.; Salem, Usama I.; Kindblom, Lars-Gunnar; Amini, Behrang; Hansson, Magnus; Meis, Jeanne M.
Abstract : Synovial sarcoma of peripheral nerve (SSPN) is rare with only 26 cases reported in English. SSPN is often mistaken for a benign or malignant peripheral nerve sheath tumor (PNST) by clinicians and pathologists. Fifteen cases of SSPN were retrieved from the pathology files of 3 institutions. All tumors arose in a nerve based on imaging and/or operative findings and the diagnoses were histologically confirmed. Neuropathic symptoms predominated in 11 women and 4 men, 19- to 62-year-old (median, 39 years) with tumors involving the ulnar (5), median (3), peroneal (3) or sciatic (2) nerve, or the L4 or T1 nerve root (2). Tumor sizes ranged from 2 to 13 cm (median, 3.8 cm). The leading clinical diagnosis was PNST (9). Treatment was surgical (14) supplemented with radiation therapy (8) and chemotherapy (6). Fourteen tumors were monophasic and 1 was biphasic; 4 had poorly differentiated (PD) foci (1 rhabdoid). Diagnoses in 12 cases were verified by fluorescence in situ hybridization, reverse transcription polymerase chain reaction or both methods. Follow-up in 14 patients (median, 32 mo) revealed that 2/4 patients with PD tumors died with pulmonary metastases; another was alive with no current evidence of disease (NED) following 2 local recurrences, while the fourth had NED. In contrast, 9/10 patients without PD tumors were alive (7 NED) and 1 died at 12 months with pulmonary infiltrates. SSPN is under-recognized clinically and histologically as it mimics benign and malignant PNST. Molecular analysis is recommended to confirm the diagnosis. PD foci, including rhabdoid areas, may portend a worse outcome, similar to non-neural–based tumors.